Bank Lending and Asset Prices in the Euro Area - Michael Frömmel; Torsten Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2006)
We examine the dynamics of bank lending to the private sector for countries of the Euro area by applying a Markov switching error correction model.We identify for Belgium, Germany, Ireland and Portugal stable, mean reverting regimes and unstable regimes with no tendency to return to the long term credit demand equation, whereas for some other countries there is only weak evidence. Furthermore, for these as well as for other countries we detect in the less stable regimes a strong co-movement with the development of the stock market. We interpret this as evidence for constraints in bank lending. In contrast, the banks? capital seems to have only marginal impact on the lending behaviour.
Keywords: C32; G21; 330; Credit demand; credit rationing; asset prices; credit channel; Kreditgeschäft; Capital Asset Pricing Model; Börsenkrise; Aktienmarkt; Bank; Schätzung; EU-Staaten; Österreich; Belgien; Finnland; Deutschland; Frankreich